ANALISIS TITIK IMPAS (Break Even Point) USAHA PENGOLAHAN IKAN SALAI PATIN DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Mastaulina Siagian; M. Ramli; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted to analyze break even point of smoked catfish (Pangasius sutchi) processing in the Koto Mesjid village. The method used in this study was a survey method with five (5) respondents. Break even point Analysis is analysis to determine break even point of company's management, thats mean there is no profit and no loss so can determine compatible price and sale. The results showed that the smoked fish processing pangasius in December 2013 was able to reach the break-even point (BEP) at Rp. 9.570.000 with total revenue (TR) Rp. 183.048.000, the total fixed costs (FC) Rp. 8.176.390 and total variable costs (VC) Rp. 759.247.000 and margin of safety (MoS) 95%. Based on the result, this bussiness had financial advantages that efficient with R/C ratio 1.19. The bussiness Constraints was lack of raw materials for processed catfish in the village.Keyword: Production, Marketing, Catfish, BEP, Kampar Regency